Análisis de estructuras de carga de dos tormentas eléctricas registradas por la red Lightning Mapping Array en el Magdalena Medio colombiano - Ardila Murillo, Brandon Steven; Soto Ríos, Edison Andrés; Argüello Barbosa, Didier; Tello Rodríguez, Heribert; López Trujillo, Jesús; Montanyà, Joan (Ingeniería, 2022)
Context: From the location of the Lightning Mapping Array (LMA) network at the borders of the municipalities of Barrancabermeja and Yondó in 2018, uninterrupted data of IC and CG flashes that occurred over this study area were taken. So far, no electrical storms have been characterized in tropical areas such as Magdalena Medio through high-resolution lightning mapping networks. Therefore, in this work, the charge structure of two thunderstorms registered by the LMA network on November 23 and 27, 2018, is determined. Method: Based on inspection methods, the bidirectional leader theory, the propagation differences of positive and negative leaders, and a data visualization algorithm, the heights of the recorded thunderstorms’ charged regions were defined. Likewise, using information from the LINET network, possible CG flashes that occurred during the studied time windows were determined along with their corresponding currents and polarities. Results: Both thunderstorms had a tripolar structure; in the November 23 storm, the height of the lower positive charge region was located between 5 and 7,5 km, the negative charge region was between 7,5 and 9 km, and the upper positive between 9 and 14,5 km. In the case of the November 27 storm, the lower positive, negative, and upper positive charge regions were located between 4 and 6 km, 6 and 8,5 km, and 8,5 and 16 km, respectively. Conclusions: In general, the heights of the charge regions in both thunderstorms are similar to those found by the COLMA network located in Santa Marta, Magdalena. Lightning leaders were corroborated which reached maximum heights of 15,88 km, slightly lower than those reported in the northern region of Colombia.